ANALISIS DAMPAK PENGARUH DARI MULTIPLAYER SERVICES PADA DAYA TARIK GAME PUBG DI KOTA BATAM - Carlos Justin Komali; Christina Chow, Jackson, Navelina, Winsley (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2023)
From this study we aim to conduct research on the influence of Multiplayer Services on the attractiveness of PUBG games and evaluate these influences using Quantitative methods. Where the quantitative research method applied to this research is based on SEM analysis methods using SPSS and AMOS applications. Where data collection in research uses questionnaires in the form of Google. In this study, several tests were carried out, including validity tests, reliability test, SEM Method, Fit Model and interpretation of hypothesis test results. The results achieved in this study are Information Quality, System Quality and Service Quality are significant and has a positive impact on System Use, also Information Quality, System Quality, Service Quality, and System Use are significant and has a positive impact on User Satisfaction